Regional scale diversity and distribution of soil inhabiting Tetracladium - Anna Lazar; Robert I. Griffiths; Tim Goodall; Lisa R. Norton; Ryan M. Mushinski; Gary D. Bending (Environmental Microbiome, 2024)
Abstract The genus Tetracladium has historically been regarded as an aquatic hyphomycete. However, sequencing of terrestrial ecosystems has shown that Tetracladium species might also be terrestrial soil and plant-inhabiting fungi. The diversity of Tetracladium species, their distribution across ecosystems, and the factors that shape community composition remain largely unknown. Using internal transcribed spacer (ITS) amplicon sequencing, we investigated the spatial distribution of Tetracladium in 970 soil samples representing the major ecosystems found across the British landscape. Species of the genus were found in 57% of the samples and across all vegetation types. The Tetracladium sequences we recovered included species common in aquatic ecosystems. However, we found five additional clades that clustered with environmental sequences previously found in terrestrial environments. The community composition of the Tetracladium OTUs was mainly related to vegetation type and soil pH. Strikingly, both taxon richness and overall abundance were highest in arable soils and showed positive relationships with soil pH. T. maxilliforme and a taxon of environmental sequences, Tetracladium group 1, was the biggest group, had the most relative abundance across ecosystems and was found in all vegetation types. Overall, this study provides insights into the community composition patterns of Tetracladium in terrestrial ecosystems and highlights the importance of vegetation characteristics in shaping Tetracladium communities.